Expanding the Lexicon : Linguistic Innovation, Morphological Productivity, and Ludicity. - Arndt-Lappe, Sabine (Dynamics of wordplay., 2018)
The creation of new lexical units and patterns has been studied in different research frameworks, focusing on either system-internal or system-external aspects, from which no comprehensive view has emerged. The volume aims to fill this gap by studying dynamic processes in the lexicon - understood in a wide sense as not being necessarily limited to the word level - by bringing together approaches directed to morphological productivity as well as approaches analyzing general types of lexical innovation and the role of discourse-related factors. The papers deal with ongoing changes as well as with historical processes of change in different languages and reflect on patterns and specific subtypes of lexical innovation as well as on their external conditions and the speakers' motivations for innovating. Moreover, the diffusion and conventionalization of innovations will be addressed. In this way, the volume contributes to understanding the complex interplay of structural, cognitive and functional factors in the lexicon as a highly dynamic domain.